Electrical conductivity monitoring of soil condition and available N with animal manure and a cover crop - Eigenberg, R.A; Doran, J.W; Nienaber, J.A; Ferguson, R.B; Woodbury, B.L (Agriculture, ecosystems & environment, 2002)
Development of sustainable agricultural management systems will depend, in part, on the ability to better use renewable resources, such as animal manure, and to synchronize the levels of soil available N with crop plant needs during the growing season. This study was conducted at the US Meat Animal Research Center in the central USA to determine whether differences in electromagnetic (EM) soil conductivity and available N levels over a growing season can be linked to feedlot manure/compost application and use of a green winter cover crop. A series of soil conductivity maps of a research cornfield were generated using global positioning system (GPS) and EM induction methods. The study site was treated over a 7-year period with manure and compost at rates matching either the phosphorus or the nitrogen requirements of silage corn (Zea mays L.). The plot was split for sub-treatments of a rye (Secale cereale L.) winter cover crop and no cover crop. Image processing techniques were used to establish electrical conductivity (EC) treatment means for each of the growing season surveys. Sequential measurement of profile weighted soil electrical conductivity (ECa) was effective in identifying the dynamic changes in available soil N, as affected by animal manure and N fertilizer treatments, during the corn-growing season. This method also clearly identified the effectiveness of cover crops in minimizing levels of available soil N before and after the corn-growing season, when soluble N is most subject to loss. The EM method for assessing soil condition provides insights into the dynamics of available N transformations that are supported by soil chemical analyses. This real-time monitoring approach could also be useful to farmers in enhancing N use efficiencies of cropping management systems and in minimizing N losses to the environment.